-6v-4=-4(v-3)

Simple and best practice solution for -6v-4=-4(v-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6v-4=-4(v-3) equation:


Simplifying
-6v + -4 = -4(v + -3)

Reorder the terms:
-4 + -6v = -4(v + -3)

Reorder the terms:
-4 + -6v = -4(-3 + v)
-4 + -6v = (-3 * -4 + v * -4)
-4 + -6v = (12 + -4v)

Solving
-4 + -6v = 12 + -4v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '4v' to each side of the equation.
-4 + -6v + 4v = 12 + -4v + 4v

Combine like terms: -6v + 4v = -2v
-4 + -2v = 12 + -4v + 4v

Combine like terms: -4v + 4v = 0
-4 + -2v = 12 + 0
-4 + -2v = 12

Add '4' to each side of the equation.
-4 + 4 + -2v = 12 + 4

Combine like terms: -4 + 4 = 0
0 + -2v = 12 + 4
-2v = 12 + 4

Combine like terms: 12 + 4 = 16
-2v = 16

Divide each side by '-2'.
v = -8

Simplifying
v = -8

See similar equations:

| -71p+2p-9p+2+43= | | y=(-.0625)x^2+.375x+(-2.05) | | -6v-4=4(v-3) | | -6v-4=-4v(v-3) | | 10(3x-1)=-100 | | 3(v+3)=-8v-2 | | -16+x=8 | | 3y+48=-3(y+2) | | (16q+4)+42=29q+20 | | (-2+v+y)(-9)= | | 5x(12-5)-9=36 | | 2x-10=3x-35 | | -5=-5y+3(y+5) | | 4ln(x-2)=-2 | | (x+31)+34=45x+21 | | -6(2x-2u-2)= | | x+2=4-2*x | | -3u+7(u-2)=-22 | | 3m-12=-6 | | 8(v+7)-2v=38 | | -(-2y-x+2)= | | 2x^2-10x=4x | | 8(v+7)+2v=38 | | (1)3.45=3(4.42) | | -1.2+0.15x=0 | | -18p-6(5-4p)=4(p-3)-12 | | 7x^2+151x-1372=0 | | 11y-8=5y+16 | | 8w-3=5w+18 | | ln(x+2)=7-ln(x+2) | | -81=6v-13v-18 | | -5x-19=0 |

Equations solver categories